THE USE OF VIDEO CONFERENCES IN MICROTEACHING PRACTICES BY PRIMARY SCHOOL TEACHER EDUCATION STUDENTS - Eri Subekti; Hesti Widiastuti; Audilla Putri Munggaran; Bella Anantha Sritumini (Jurnal Cakrawala Pendas, 2023)
The emergence of the Covid-19 pandemic in the world affects the implementation of the learning in the Microteaching course which requires students to make simulations of learning activities in class. One solution that could be applied to achieve learning targets was using video conferencing. This study aimed to analyze the implementation process of teaching practices using video conference in Microteaching course by Primary School Teacher Education (PGSD) student. This study applied a quantitative descriptive method with microteaching assessment rubric instruments. Quantitative calculations were carried out by calculating the percentage of the total score obtained from each criterion of the microteaching assessment rubric, then converted into qualitative data through the percentage table of learning outcomes assessment criteria. Based on the results, it can be concluded that the student participants could achieve all criteria of microteaching process with good results. The use of learning media became the criterion which most students achieved very good results. It is followed by the criterion of the use of teaching methods, delivering material, and understanding concepts which most students achieved good results. Meanwhile, the criteria of opening, class management, and closing are still in a fair category and must be improved. Munculnya pandemi Covid-19 di dunia mempengaruhi pelaksanaan pembelajaran pada mata kuliah Microteaching yang mengharuskan mahasiswa melakukan simulasi kegiatan pembelajaran di kelas. Salah satu solusi yang dapat diterapkan untuk mencapai target pembelajaran adalah dengan menggunakan video conference. Penelitian ini bertujuan untuk menganalisis proses pelaksanaan praktik mengajar menggunakan video conference pada mata kuliah microteaching oleh mahasiswa Pendidikan Guru Sekolah Dasar (PGSD). Penelitian ini menggunakan metode deskriptif kuantitatif dengan instrumen rubrik penilaian microteaching. Perhitungan kuantitatif dilakukan dengan menghitung persentase jumlah skor yang diperoleh dari setiap kriteria rubrik penilaian microteaching, kemudian dikonversikan ke dalam data kualitatif melalui tabel persentase kriteria penilaian hasil belajar. Berdasarkan hasil penelitian, dapat disimpulkan bahwa mahasiswa peserta dapat mencapai semua kriteria proses microteaching dengan hasil yang baik. Penggunaan media pembelajaran menjadi kriteria yang paling banyak mendapatkan nilai sangat baik. Diikuti dengan kriteria penggunaan metode mengajar, penyampaian materi, dan pemahaman konsep yang sebagian besar mahasiswa memperoleh hasil yang baik. Sementara itu, kriteria membuka pelajaran, pengelolaan kelas, dan menutup pelajaran masih dalam kategori cukup dan harus ditingkatkan.